2017
DOI: 10.2109/jcersj2.17019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CO<sub>2</sub> absorption reaction of Li<sub>4</sub>SiO<sub>4</sub> on the basis of madelung potential of Li site in crystal structure

Abstract: We estimated site potentials for respective Li ions in the unit cell of Li 4 SiO 4 crystal structure using the VESTA program and examined relation between the estimated site potentials and reactivity of the respective Li ions to CO 2 . Values of the estimated site potentials for the respective Li ions were distributed over a range of the shallowest level (¹11.6 V) to the deepest level (¹17.3 V). It is forecasted that the depth of these potentials would relate with reaction between CO 2 and the respective Li io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Oh-ishi et al reported the relation between the calculated site potentials of the respective Li ions and their reactivity to CO 2 for the reaction of Li 4 SiO 4 with CO 2 . 32 The calculation indicated that the depth of these potentials of Li ions would be related to the reaction between CO 2 and the respective Li ions in Li 4 SiO 4 . According to this consideration, the site potentials of Mn 4+ in the unit cells of SrMnO 3 and the as-prepared SFM sample with x = 0.5 were calculated using the MADEL program in the VESTA program.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Oh-ishi et al reported the relation between the calculated site potentials of the respective Li ions and their reactivity to CO 2 for the reaction of Li 4 SiO 4 with CO 2 . 32 The calculation indicated that the depth of these potentials of Li ions would be related to the reaction between CO 2 and the respective Li ions in Li 4 SiO 4 . According to this consideration, the site potentials of Mn 4+ in the unit cells of SrMnO 3 and the as-prepared SFM sample with x = 0.5 were calculated using the MADEL program in the VESTA program.…”
Section: Discussionmentioning
confidence: 96%
“…The Madelung potentials, which are comparable to the site potentials in unit cells of crystal structures, were calculated to estimate the stability of the ions in compounds. Oh-ishi et al reported the relation between the calculated site potentials of the respective Li ions and their reactivity to CO 2 for the reaction of Li 4 SiO 4 with CO 2 . The calculation indicated that the depth of these potentials of Li ions would be related to the reaction between CO 2 and the respective Li ions in Li 4 SiO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Li4SiO4 has excellent CO2 sorption capacity at the temperature range of 450-700 °C, with a theoretical value of 36.7 wt%. [39][40][41][42] The CO2 sorption performance of Li4SiO4 is controlled by several factors. So far, several models have been proposed for the CO2 sorption and desorption processes over Li4SiO4, which include double shell model, Avrami-Erofeev model, shrinking core model, and unreacted-core model.…”
Section: Co2 Sorption/desorption Models For Li4sio4mentioning
confidence: 99%
“…17 The degradation of these devices arise from instability of the perovskite structure type hybrid compounds and can also be understood from Madelung electrostatic potential analysis. 18 Furthermore, it has also been shown that the stability of oxides such as Li 19 On the other hand, lattice site potential can be used for the estimation of the oxygen to metal charge transfer and bandgap of perovskite type ABO 3 oxides using an ionic model developed by Zaanen et al 20 and demonstrated in a large number of oxides by Torrance et al 21 and Arima et al 22 Kato et al employed lattice site potential analysis to show that the valence band structure can be tailored by designing the stacking sequence of layers of a number of layered compounds BiOX (X ¼ Cl, Br, I), Bi 4 NbO 8 X (X ¼ Cl, Br), Bi 2 GdO 4 X (X ¼ Cl, Br), and SrBiO 2 X (X ¼ Cl, Br, I) and therefore, lattice site potential analysis may be useful for designing new photocatalysts. 23 Here we look back at the development of Madelung electrostatic potential and lattice site potential only for perovskite type ABO 3 oxides.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Furthermore, it has also been shown that the stability of oxides such as Li 4 SiO 4 towards the reaction Li 4 SiO 4 + CO 2 → Li 2 SiO 3 + Li 2 CO 3 has direct consequence on the CO 2 capture and storage abilities and recent study by Oh-ishi et al had successfully employed lattice site potentials analysis of all Li + ions in the unit cells of Li 4 SiO 4 , Li 2 SiO 3 , and Li 2 CO 3 to evaluate the extraordinary stability. 19 …”
Section: Introductionmentioning
confidence: 99%